Texturing method of crystalline silicon solar cell silicon wafer
Through technical means such as laser crystallization and alkali polishing, the problem of non -crystal silicon layer and line marks on the surface of the silicon silicon solar cell silicon wafer after cutting after cutting is solved.
Patent Information
- Application Number
- CN202411433243.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-28
AI Technical Summary
In the existing crystalline silicon solar cell shroud making process, the cutting process causes amorphous silicon layer and wire marks to form on the surface of the silicon wafer, affecting the uniformity and reflectivity of the suede, and the process time is long, affecting production capacity.
Using the method of laser primary crystallization, one -alkaline polishing, laser secondary crystallization, secondary alkali polishing, and HF/HNO3 system pre -processing method, remove the amorphous silicon layer and line marks on the surface of the silicon wafer, and generate a uniform pyramid surface. And shorten the time of fluff.
The uniformity and reflectivity of the pyramid surface of the silicon wafer surface are realized, shortening the ploment time and increased production capacity.
Smart Images

Figure CN119384062A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of solar cells, and in particular to a texturing method for a crystalline silicon solar cell silicon wafer. Background Art
[0002] Texturing is the first step in the preparation process of crystalline silicon solar cells and is an important means to improve the optical performance of the cells. At present, the texturing process of solar cells in the production line is the conventional "one-step" alkaline texturing. The specific process is: first put the cut single crystal silicon wafer into the KOH / H2O2 tank for pre-cleaning, and then put it into the KOH / additive mixed solution for reaction at ~80℃ for 7~8min to form a positive pyramid velvet surface with a velvet size of 1~2μm and a silicon wafer surface reflectivity of ~10%.
[0003] At present, the above process faces the following technical problems: (1) During the process of cutting silicon wafers, the diamond wire will repeatedly apply external force to squeeze the silicon wafer, causing the atomic arrangement on its surface to change, thereby forming an amorphous silicon layer on the surface of the silicon wafer. The amorphous silicon layer has inconsistent reaction characteristics with the crystalline silicon layer during the subsequent wet cleaning and etching process, resulting in inconsistent velvet surface in the end.
[0004] (2) There are a lot of line marks on the surface of the silicon wafer after cutting (such as Figure 3 As shown in the figure, during the texturing process, the reaction rates of silicon atoms in the line mark area and the non-line mark area in the alkaline solution are inconsistent, resulting in uneven suede surfaces in the subsequent line mark and non-line mark areas.
[0005] (3) The conventional alkali velveting process usually takes 7 to 8 minutes, which is relatively long and affects the increase in production capacity.
[0006] In view of this, it is necessary to develop a new process that can achieve rapid and uniform texturing of silicon wafers. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a texturing method for crystalline silicon solar cell silicon wafers. The present invention can greatly reduce the texturing time by performing "laser primary crystallization → primary alkali polishing → laser secondary crystallization → secondary alkali polishing → HF / HNO3 system pretreatment" on the silicon wafer, and the pyramid velvet surface generated on the surface of the silicon wafer is more uniform, which can effectively reduce the velvet reflectivity.
[0008] The specific technical solution of the present invention is: a method for texturing a crystalline silicon solar cell silicon wafer, which specifically includes the following steps: S1, laser crystallization treatment of the entire surface of the original silicon wafer after diamond wire cutting, so that the amorphous silicon layer on the surface of the silicon wafer is converted into a crystalline silicon layer.
[0009] As described in the background technology section, an amorphous silicon layer will be formed on the shallow surface of the silicon wafer after diamond wire cutting. The reaction characteristics of the amorphous silicon layer are inconsistent with those of the crystalline silicon layer during the subsequent wet cleaning and etching process, resulting in an inconsistent velvet surface. To this end, the present invention uses laser crystallization to process the entire surface of the silicon wafer, so that most of the amorphous silicon layer is converted into a crystalline silicon layer.
[0010] S2. Alkaline polishing is performed to remove the crystalline silicon layer on the surface of the silicon wafer.
[0011] After the silicon wafer is subjected to alkali polishing, the crystalline silicon layer on the surface can be removed. The present invention first converts the amorphous silicon layer into a crystalline silicon layer and then performs alkali polishing, rather than directly performing alkali polishing on the amorphous silicon layer. The reason is that the corrosion rate of the amorphous silicon layer on the surface of the initial silicon wafer in alkali is slower than that of the crystalline silicon layer, resulting in the inability to effectively remove the amorphous silicon layer under certain alkali polishing conditions.
[0012] S3, laser patterning and secondary crystallization treatment is performed on the bottom of the line marks and grooves formed by diamond wire cutting on the silicon wafer, so that the residual amorphous silicon layer in the area is converted into a crystalline silicon layer.
[0013] Since the friction force between the bottom area of the diamond wire groove and the silicon wafer is greater than that between the side area during the cutting process, the thickness of the amorphous silicon layer at the bottom of the wire groove is often greater than that of the amorphous silicon layer on the side of the wire groove. However, it is difficult to effectively convert all the amorphous silicon at the bottom of the wire groove into crystalline silicon during the laser primary crystallization process. For this reason, the present invention uses laser secondary crystallization to fully convert the bottom of the wire groove of the silicon wafer into crystalline silicon.
[0014] S4. A secondary alkaline polishing is performed to remove the newly formed crystalline silicon layer on the surface of the silicon wafer line marks and grooves.
[0015] S5. Pre-treat the silicon wafer by immersing it in a HF / HNO3 mixed solution to form a porous silicon layer on the surface of the silicon wafer; the mass concentration of HF in the HF / HNO3 mixed solution is greater than that of HNO3.
[0016] In order to shorten the subsequent texturing time of silicon wafers and improve production efficiency, the present invention places the silicon wafers after the above-mentioned secondary polishing into a HF / HNO3 mixed solution for pretreatment, and introduces a "porous silicon" structure on the surface of the silicon wafer after pretreatment. Since the "porous silicon" structure has a large specific surface area, the reaction rate between the silicon surface and the alkali will be accelerated during the subsequent alkali texturing process, thereby shortening the entire texturing time. It should be noted that the HNO3 content in the HF / HNO3 mixed solution needs to be less and the HF content needs to be more, so that the oxidizing effect of HNO3 on the surface of the silicon wafer can be weaker than the solubility effect of HF on silicon dioxide, thereby breeding more "porous silicon" structures on the surface of the silicon wafer.
[0017] S6. Alkali texturing to obtain a silicon wafer with a uniform pyramid texture on the surface.
[0018] Due to the "porous silicon" structure on the surface of the silicon wafer, its specific surface area is larger than that of a normal polished surface, and it is exposed to relatively more alkaline solution, so the initial silicon wafer reaction rate is faster, which can effectively reduce the preparation time required for the final velvet formation. In addition, since the present invention uses two laser crystallization and alkali polishing processes to remove the line marks and amorphous silicon layer on the surface of the initially cut silicon wafer, the velvet formed in the subsequent alkali velvet preparation process has a higher uniformity, and the corresponding velvet reflectivity tends to be further reduced than the conventional velvet reflectivity, which can allow more sunlight to enter the silicon wafer substrate.
[0019] Preferably, in S1, the silicon wafer is an N-type single crystal silicon wafer.
[0020] Preferably, in S1, the laser wavelength of the laser primary crystallization treatment is 500-600 nm, the pulse time is 5-20 ns, the frequency is 10-20 KHz, the power is 1-5 W, and the time is 1-10 s.
[0021] Preferably, in S2, the alkali concentration in the alkali polishing solution of the first alkali polishing is 1.7-2.2 wt %.
[0022] Preferably, in S2, the temperature of the first alkali polishing is 75-85°C, the time is 1-5 min, and the thinning amount is 0.10-0.20 g.
[0023] Preferably, in S3, the laser wavelength of the laser patterning secondary crystallization treatment is 500-600 nm, the pulse time is 5-20 ns, the frequency is 1-10 KHz, the power is 5-10 W, and the time is 1-20 s.
[0024] Since the bottom of the silicon wafer line mark groove is subjected to greater external force from the diamond wire during cutting, the amorphous silicon layer there is thicker than the side and top areas of the line mark; in order to fully transform this part of the amorphous silicon layer into a crystalline silicon layer, the laser power in the laser patterning secondary crystallization process should be slightly higher than that in the laser primary crystallization process. Appropriate high-power lasers help to quickly increase the temperature of the silicon wafer processing area, and the temperature diffusion depth is also deeper, and at the same time, it will not cause significant laser damage to the silicon surface.
[0025] In addition, the laser frequency in laser patterning secondary crystallization also needs to be low, and different laser frequencies will significantly affect the energy of a single laser beam. When the laser output power is timed, the lower the frequency, the greater the energy of the single laser beam, and vice versa. This is because the single laser energy is related to the repetition frequency of the laser, and the output power is the product of the single laser energy and the repetition frequency. Specifically: the repetition frequency refers to the number of pulses emitted by the laser per unit time. When the output power is constant, the high or low repetition frequency will affect the energy of a single pulse. Increasing the repetition frequency will lead to a decrease in the energy of a single pulse, because the output power is fixed, and more pulses mean that the energy carried by each pulse is reduced; if the frequency increases, the energy of a single pulse will decrease accordingly to keep the output power unchanged. This is because the output power is the product of the single pulse energy and the repetition frequency, and increasing the frequency will inevitably lead to a decrease in the energy of a single pulse. Therefore, the single energy of low-frequency lasers is often large, which helps to fully transform the amorphous silicon layer at the bottom of the silicon wafer line mark groove into a crystalline silicon layer from another perspective.
[0026] Preferably, in S4, the alkali concentration in the alkali polishing solution of the secondary alkali polishing is 1.7-2.2 wt %.
[0027] Preferably, in S4, the temperature of the secondary alkali polishing is 75-85°C, the time is 1-3 min, and the thinning amount is 0.05-0.20 g.
[0028] Preferably, in S5, the HF / HNO3 mixed solution is prepared by mixing 45-55wt% HF solution and 65-75wt% HNO3 solution in a volume ratio of 2:1-7:1.
[0029] Preferably, in S5, the pretreatment temperature is 30-35° C. and the time is 30-120 s.
[0030] Preferably, in S6, the alkali texturing uses 1.6-2.0 wt% alkali solution, the alkali texturing temperature is 75-85° C., and the time is 5-7 min.
[0031] Preferably, in S6, the surface size of the pyramid surface formed after alkali texturing is 1-2 μm, and the surface reflectivity of the silicon wafer is less than 10%.
[0032] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention can greatly reduce the alkali texturing time by performing "laser primary crystallization → primary alkali polishing → laser secondary crystallization → secondary alkali polishing → HF / HNO3 system pretreatment" on the silicon wafer, and the pyramid velvet surface generated on the surface of the silicon wafer is more uniform, which can effectively reduce the velvet reflectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1This is a scanning electron microscope image of the silicon wafer surface after diamond wire cutting.
[0034] Figure 2 These are the Raman spectra of the initial silicon wafer cut surface and after laser primary crystallization.
[0035] Figure 3 Schematic diagram of the line marks on the silicon wafer surface after diamond wire cutting.
[0036] Figure 4 Photos of the surface appearance of silicon wafers (a) after alkali polishing and (b) after the introduction of porous silicon.
[0037] Figure 5 Scanning electron microscope images of the surface morphology of silicon wafers (a) after conventional alkali texturing in comparative example 1 and (b) after rapid and uniform texturing in example 1.
[0038] Figure 6 This is the reflectivity curve of the silicon wafer after conventional texturing in comparative example 1 and rapid texturing in example 1. DETAILED DESCRIPTION
[0039] The present invention will be further described below in conjunction with the embodiments.
[0040] Overall embodiment A method for texturing a crystalline silicon solar cell silicon wafer comprises the following steps: S1. The entire surface of the original silicon wafer after diamond wire cutting is laser crystallized once to convert the amorphous silicon layer on the surface of the silicon wafer into a crystalline silicon layer.
[0041] After diamond wire cutting, an amorphous silicon layer will be formed on the shallow surface of the silicon wafer. The reaction characteristics of the amorphous silicon layer are inconsistent with those of the crystalline silicon layer during the subsequent wet cleaning and etching process, resulting in an inconsistent velvet surface. To this end, the present invention uses laser crystallization to process the entire surface of the silicon wafer, so that most of the amorphous silicon layer is converted into a crystalline silicon layer.
[0042] In some specific implementation cases, in S1, the silicon wafer is an N-type single crystal silicon wafer.
[0043] In some specific implementation cases, in S1, the laser wavelength of the laser primary crystallization treatment is 500-600 nm, the pulse time is 5-20 ns, the frequency is 10-20 KHz, the power is 1-5 W, and the time is 1-10 s.
[0044] S2. Alkali polishing to remove the shallow surface layer of the silicon wafer. After the silicon wafer is subjected to alkaline polishing, the crystalline silicon layer on the surface of the silicon wafer can be removed.
[0045] In some specific implementation cases, in S2, the alkali concentration in the alkali polishing solution of the first alkali polishing is 1.7-2.2 wt %.
[0046] In some specific implementation cases, in S2, the temperature of the first alkali polishing is 75-85°C, the time is 1-5 minutes, and the thinning amount is 0.10-0.20g.
[0047] S3, laser patterning and secondary crystallization treatment is performed on the bottom of the line marks and grooves formed by diamond wire cutting on the silicon wafer, so that the residual amorphous silicon layer in the area is converted into a crystalline silicon layer.
[0048] Since the friction force between the bottom area of the diamond wire groove and the silicon wafer is greater than that between the side area during the cutting process, the thickness of the amorphous silicon layer at the bottom of the wire groove is often greater than that of the amorphous silicon layer on the side of the wire groove. However, it is difficult to effectively convert all the amorphous silicon at the bottom of the wire groove into crystalline silicon during the laser primary crystallization process. For this reason, the present invention uses laser secondary crystallization to fully convert the bottom of the wire groove of the silicon wafer into crystalline silicon.
[0049] In some specific implementation cases, in S3, the laser wavelength of the laser patterning secondary crystallization process is 500-600 nm, the pulse time is 5-20 ns, the frequency is 1-10 KHz, the power is 5-10 W, and the time is 1-20 s.
[0050] S4. A secondary alkaline polishing is performed to remove the newly formed crystalline silicon layer on the surface of the silicon wafer line marks and grooves.
[0051] In some specific implementation cases, in S4, the alkali concentration in the alkali polishing solution of the secondary alkali polishing is 1.7-2.2 wt %.
[0052] In some specific implementation cases, in S4, the temperature of the secondary alkali polishing is 75-85° C., the time is 1-3 min, and the thinning amount is 0.05-0.20 g.
[0053] S5. Pre-treat the silicon wafer by immersing it in a HF / HNO3 mixed solution to form a porous silicon layer on the surface of the silicon wafer; the mass concentration of HF in the HF / HNO3 mixed solution is greater than that of HNO3.
[0054] In order to shorten the subsequent texturing time of silicon wafers and improve production efficiency, the present invention places the silicon wafers after the above-mentioned secondary polishing into a HF / HNO3 mixed solution of an HF-rich system for pretreatment, and introduces a "porous silicon" structure on the surface of the silicon wafer after treatment. Since the "porous silicon" structure has a large specific surface area, the reaction rate between the silicon surface and the alkali will be accelerated during the subsequent alkali texturing process, thereby shortening the entire texturing time. It should be noted that the HNO3 content in the HF / HNO3 mixed solution needs to be less and the HF content needs to be more, so that the oxidizing effect of HNO3 on the surface of the silicon wafer is weaker than the solubility effect of HF on silicon dioxide, so that more "porous silicon" structures can be grown on the surface of the silicon wafer.
[0055] In some specific implementation cases, in S5, the HF / HNO3 mixed solution is prepared by mixing 45-55wt% HF solution and 65-75wt% HNO3 solution in a volume ratio of 2:1-7:1.
[0056] In some specific implementation cases, in S5, the pretreatment temperature is 30-35° C. and the time is 30-120 s.
[0057] S6. Alkali texturing to obtain a silicon wafer with a uniform pyramid texture on the surface.
[0058] Due to the "porous silicon" structure on the surface of the silicon wafer, its specific surface area is larger than that of a normal polished surface, and it is exposed to relatively more alkaline solution, so the initial silicon wafer reaction rate is faster, which can effectively reduce the preparation time required for the final velvet formation. In addition, since the present invention uses two laser crystallization and alkali polishing processes to remove the line marks and amorphous silicon layer on the surface of the initially cut silicon wafer, the velvet formed in the subsequent alkali velvet preparation process has a higher uniformity, and the corresponding velvet reflectivity tends to be further reduced than the conventional velvet reflectivity, which can allow more sunlight to enter the silicon wafer substrate.
[0059] In some specific implementation cases, in S6, the alkali texturing uses 1.6-2.0 wt% alkali solution, the alkali texturing temperature is 75-85° C., and the time is 5-7 min.
[0060] In some specific implementation cases, in S6, the velvet surface size of the pyramid velvet surface formed after alkali texturing is 1-2 μm, and the surface reflectivity of the silicon wafer is less than 10%.
[0061] Specific Examples and Comparative Examples Example 1 A method for texturing a crystalline silicon solar cell silicon wafer comprises the following steps: S1, select the original N-type single crystal silicon wafer after diamond wire cutting (such as Figure 1 As shown in the figure, the original N-type single crystal silicon wafer is subjected to a laser crystallization treatment on the entire surface, so that the amorphous silicon layer on the surface of the silicon wafer is converted into a crystalline silicon layer. The laser wavelength of the laser crystallization treatment is 532nm, the pulse time is 15ns, the frequency is 12KHz, the power is 3W, and the time is 4s.
[0062] Figure 2 The Raman spectra of the initial silicon wafer surface and the surface after laser crystallization are shown in Figure 2. The Raman spectrum peak of amorphous silicon on the surface of the silicon wafer after initial cutting is located at 480cm -1 The crystallization rate is about 42%, and after laser crystallization, the crystallization rate increases to about 87%. The main Raman peak increases from 480cm -1 Move to 520cm -1 .
[0063] S2. Alkali polishing to remove the crystalline silicon layer on the surface of the silicon wafer: immerse the silicon wafer in an alkaline polishing solution for alkaline polishing, wherein the KOH concentration in the alkaline polishing solution is 2.1wt%, the temperature is 78°C, the time is 3.5min, and the thinning amount is 0.13g.
[0064] S3. Perform laser patterning secondary crystallization on the bottom of the groove formed by diamond wire cutting on the silicon wafer, so that the residual amorphous silicon layer in the area is fully converted into a crystalline silicon layer. The laser wavelength of the laser patterning secondary crystallization treatment is 532nm, the pulse time is 8ns, the frequency is 5KHz, the power is 7W, and the time is 13s.
[0065] S4. Secondary alkaline polishing to remove the newly formed crystalline silicon layer on the surface of the silicon wafer line trace groove: immerse the silicon wafer in an alkaline polishing solution for secondary alkaline polishing. The alkaline polishing solution has a KOH concentration of 2.2wt%, a temperature of 80°C, a time of 2 minutes, and a thinning amount of 0.09g.
[0066] S5, pre-treating the silicon wafer by immersing it in a HF / HNO3 mixed solution to form a porous silicon layer on the surface of the silicon wafer. The HF / HNO3 mixed solution is prepared by mixing 49wt% HF solution and 69wt% HNO3 solution in a volume ratio of 5:1. The pre-treating temperature is 32°C and the time is 60s. Figure 4 Shown are photos of the surface appearance of the silicon wafer after alkali polishing (a) and after the introduction of porous silicon (b).
[0067] S6, alkali texturing the silicon wafer to obtain a silicon wafer with a uniform pyramid texture on the surface. The KOH concentration in the alkali texturing solution is 1.7wt%, the temperature is 80°C, and the time is 6.0min. The size of the pyramid texture formed after alkali texturing is about 1.3μm (e.g. Figure 5 (b)), the reflectivity of the silicon wafer surface is about 9.5% (as shown in Figure 6 shown).
[0068] Comparative Example 1 Comparative Example 1 adopts a conventional texturing process, which specifically includes the following steps: S1. Select the original N-type single crystal silicon wafer after diamond wire cutting, put it into a tank containing KOH and H2O2 for pre-cleaning, wherein the concentration of KOH is 0.7wt% and the concentration of H2O2 is 0.5wt%, to remove impurities such as surface organic matter and oil stains.
[0069] S2, the obtained silicon wafer was placed in a 1.7wt% KOH solution and reacted at 80°C for 7.5min to form a positive pyramid velvet surface with a size of about 1.2μm (such as Figure 5 (a)), the reflectivity of the silicon wafer surface is about 10.5% (as shown in Figure 6shown).
[0070] Comparative Example 2 The main difference between Comparative Example 2 and Example 1 is that "laser patterning secondary crystallization treatment + secondary alkali polishing" is not performed (i.e., S3 and S4 in Example 1 are not included), and specifically includes the following steps: S1. Select the original N-type single crystal silicon wafer after diamond wire cutting, and perform laser crystallization on the entire surface of the original N-type single crystal silicon wafer to convert the amorphous silicon layer on the surface of the silicon wafer into a crystalline silicon layer. The laser wavelength of the laser crystallization treatment is 532nm, the pulse time is 15ns, the frequency is 12KHz, the power is 3W, and the time is 4s.
[0071] S2. Alkali polishing to remove the crystalline silicon layer on the surface of the silicon wafer: immerse the silicon wafer in an alkaline polishing solution for alkaline polishing; wherein, the KOH concentration in the alkaline polishing solution is 2.1wt%, the temperature is 78°C, the time is 3.5min, and the thinning amount is 0.13g.
[0072] S3, pre-treating the silicon wafer by immersing it in a HF / HNO3 mixed solution to form a porous silicon layer on the surface of the silicon wafer. The HF / HNO3 mixed solution is prepared by mixing 49wt% HF solution and 69wt% HNO3 solution in a volume ratio of 5:1. The pre-treating temperature is 32°C and the time is 60s.
[0073] S4, performing alkali texturing on the silicon wafer to obtain a silicon wafer having a pyramid texture on the surface, wherein the KOH concentration in the alkali texturing solution is 1.7 wt %, the temperature is 80° C., and the time is 6.8 min.
[0074] Comparative Example 3 The main difference between Comparative Example 3 and Example 1 is that the silicon wafer is not pretreated in the HF / HNO3 mixed solution before alkali texturing (i.e., S5 in Example 1 is not included), and specifically comprises the following steps: S1. Select the original N-type single crystal silicon wafer after diamond wire cutting, and perform laser crystallization on the entire surface of the original N-type single crystal silicon wafer to convert the amorphous silicon layer on the surface of the silicon wafer into a crystalline silicon layer. The laser wavelength of the laser crystallization treatment is 532nm, the pulse time is 15ns, the frequency is 12KHz, the power is 3W, and the time is 4s.
[0075] S2. Alkali polishing to remove the crystalline silicon layer on the surface of the silicon wafer: immerse the silicon wafer in an alkaline polishing solution for alkaline polishing; wherein, the KOH concentration in the alkaline polishing solution is 2.1wt%, the temperature is 78°C, the time is 3.5min, and the thinning amount is 0.13g.
[0076] S3. Perform laser patterning secondary crystallization on the bottom of the groove formed by diamond wire cutting on the silicon wafer, so that the residual amorphous silicon layer in the area is fully converted into a crystalline silicon layer. The laser wavelength of the laser patterning secondary crystallization treatment is 532nm, the pulse time is 8ns, the frequency is 5KHz, the power is 7W, and the time is 13s.
[0077] S4. Secondary alkaline polishing to remove the newly formed crystalline silicon layer on the surface of the silicon wafer line trace groove: immerse the silicon wafer in an alkaline polishing solution for secondary alkaline polishing. The alkaline polishing solution has a KOH concentration of 2.2wt%, a temperature of 80°C, a time of 2 minutes, and a thinning amount of 0.09g.
[0078] S5, performing alkali texturing on the silicon wafer to obtain a silicon wafer having a pyramid texture on the surface, wherein the KOH concentration in the alkali texturing solution is 1.7 wt %, the temperature is 80° C., and the time is 7.2 min.
[0079] Comparative Example 4 The main difference between Comparative Example 4 and Example 1 is that in the HF / HNO3 mixed solution of S5, the HF content is less than HNO3, and specifically comprises the following steps: S1. Select the original N-type single crystal silicon wafer after diamond wire cutting, and perform laser crystallization on the entire surface of the original N-type single crystal silicon wafer to convert the amorphous silicon layer on the surface of the silicon wafer into a crystalline silicon layer. The laser wavelength of the laser crystallization treatment is 532nm, the pulse time is 15ns, the frequency is 12KHz, the power is 3W, and the time is 4s.
[0080] S2. Alkali polishing to remove the crystalline silicon layer on the surface of the silicon wafer: immerse the silicon wafer in an alkaline polishing solution for alkaline polishing, wherein the KOH concentration in the alkaline polishing solution is 2.1wt%, the temperature is 78°C, the time is 3.5min, and the thinning amount is 0.13g.
[0081] S3. Perform laser patterning secondary crystallization on the bottom of the groove formed by diamond wire cutting on the silicon wafer, so that the residual amorphous silicon layer in the area is fully converted into a crystalline silicon layer. The laser wavelength of the laser patterning secondary crystallization treatment is 532nm, the pulse time is 8ns, the frequency is 5KHz, the power is 7W, and the time is 13s.
[0082] S4. Secondary alkaline polishing to remove the newly formed crystalline silicon layer on the surface of the silicon wafer line trace groove: immerse the silicon wafer in an alkaline polishing solution for secondary alkaline polishing. The alkaline polishing solution has a KOH concentration of 2.2wt%, a temperature of 80°C, a time of 2 minutes, and a thinning amount of 0.09g.
[0083] S5, pre-treating the silicon wafer by immersing it in a HF / HNO3 mixed solution to form a porous silicon layer on the surface of the silicon wafer. The HF / HNO3 mixed solution is prepared by mixing 49wt% HF solution and 69wt% HNO3 solution in a volume ratio of 1:3. The pre-treating temperature is 32°C and the time is 60s.
[0084] S6, performing alkali texturing on the silicon wafer to obtain a silicon wafer having a pyramid texture on the surface, wherein the KOH concentration in the alkali texturing solution is 1.7 wt %, the temperature is 80° C., and the time is 7.0 min.
[0085] Comparative Example 5 The main difference between Comparative Example 5 and Example 1 is that the secondary laser crystallization processing parameters of S3 are the same as the primary laser crystallization parameters of S1, and specifically include the following steps: S1. Select the original N-type single crystal silicon wafer after diamond wire cutting, and perform laser crystallization on the entire surface of the original N-type single crystal silicon wafer to convert the amorphous silicon layer on the surface of the silicon wafer into a crystalline silicon layer. The laser wavelength of the laser crystallization treatment is 532nm, the pulse time is 15ns, the frequency is 12KHz, the power is 3W, and the time is 4s.
[0086] S2. Alkali polishing to remove the crystalline silicon layer on the surface of the silicon wafer: immerse the silicon wafer in an alkaline polishing solution for alkaline polishing, wherein the KOH concentration in the alkaline polishing solution is 2.1wt%, the temperature is 78°C, the time is 3.5min, and the thinning amount is 0.13g.
[0087] S3, performing laser patterning secondary crystallization treatment on the bottom of the line mark groove formed by diamond wire cutting on the silicon wafer, so that the residual amorphous silicon layer in the area is converted into a crystalline silicon layer. The laser wavelength of the laser patterning secondary crystallization treatment is 532nm, the pulse time is 15ns, the frequency is 12KHz, the power is 3W, and the time is 2s.
[0088] S4. Secondary alkaline polishing to remove the newly formed crystalline silicon layer on the surface of the silicon wafer line marks and grooves: immerse the silicon wafer in an alkaline polishing solution for secondary alkaline polishing. The alkaline polishing solution has a KOH concentration of 2.2wt%, a temperature of 80°C, a time of 2.3min, and a thinning amount of 0.11g.
[0089] S5, pre-treating the silicon wafer by immersing it in a HF / HNO3 mixed solution to form a porous silicon layer on the surface of the silicon wafer. The HF / HNO3 mixed solution is prepared by mixing 49wt% HF solution and 69wt% HNO3 solution in a volume ratio of 5:1. The pre-treating temperature is 32°C and the time is 60s.
[0090] S6, performing alkali texturing on the silicon wafer to obtain a silicon wafer having a uniform pyramid texture on the surface, wherein the KOH concentration in the alkali texturing solution is 1.7 wt %, the temperature is 80° C., and the time is 6.5 min.
[0091] Performance comparison The silicon wafers obtained in the above examples and comparative examples were tested for various properties, and the results are shown in the following table: First, for Example 1, it adopts secondary laser crystallization + alkali polishing with the introduction of "porous silicon" pretreatment, which can quickly prepare a uniform velvet surface on the surface of the silicon wafer, which not only saves the velvet making process time, but also can further reduce the reflectivity of the silicon wafer surface, which is helpful to improve the optical performance, and the overall velvet making process performance is optimal.
[0092] Secondly, for Comparative Example 1, since there are a large number of line marks and amorphous silicon layers on the surface of the initially cut silicon wafer, this will not only affect the subsequent reaction uniformity of the silicon wafer in the alkaline solution, resulting in a high reflectivity; at the same time, the reaction rate of the amorphous silicon layer is often slower than that of the crystalline silicon layer, which will further extend the entire texturing process time, and thus the texturing process has the worst performance.
[0093] For Comparative Example 2, since "laser patterning secondary crystallization treatment + secondary alkaline polishing" was not performed, the amorphous silicon layer at the bottom of the line mark groove could not be effectively transformed into a crystalline silicon layer during the laser primary crystallization process, resulting in the need for additional reaction time for further removal during the subsequent texturing process. In addition, the velvet surface at this location is inconsistent with the velvet surface formed in other areas, which not only affects the overall velvet uniformity, but also limits the further reduction of surface reflectivity.
[0094] For Comparative Example 3, since the silicon wafer was not pretreated with "porous silicon" before alkali texturing, the silicon wafer lacked many nucleation centers during the alkali texturing process, the texturing time was correspondingly prolonged, and the reflectivity was slightly higher.
[0095] For Comparative Example 4, since the HF content is lower than the HNO3 content during the pretreatment process, the oxidizing property of HNO3 in the solution is greater than the solubility of HF, and the effect on the silicon wafer is similar to "polishing", so it is impossible to effectively introduce "porous silicon" on the surface of the silicon wafer, resulting in fewer nucleation centers on the surface of the silicon wafer, and the overall process performance is lower than that of Example 1.
[0096] Finally, for Comparative Example 5, although it is similar to the scheme in Example 1, it also adopts the method of secondary laser crystallization + alkali polishing with the introduction of "porous silicon" pretreatment, but because the laser parameters in the secondary laser crystallization process are the same as those in the primary crystallization, it is difficult to effectively transform the amorphous silicon layer at the bottom of the line mark groove into a crystalline silicon layer during the process, so that this area will still partially affect the texturing performance. The overall performance is slightly lower than that of Example 1, but better than Comparative Examples 1-4.
[0097] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0098] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for texturing a crystalline silicon solar cell silicon wafer, characterized in that include: S1. Performing a laser crystallization treatment on the entire surface of the silicon wafer after diamond wire cutting to convert the amorphous silicon layer on the surface of the silicon wafer into a crystalline silicon layer; S2, an alkali polishing to remove the crystalline silicon layer on the surface of the silicon wafer; S3, performing a laser patterning secondary crystallization process on the bottom of the line mark groove formed by diamond wire cutting on the silicon wafer, so that the residual amorphous silicon layer in the area is converted into a crystalline silicon layer; S4, secondary alkali polishing to remove the crystalline silicon layer on the surface of the silicon wafer line mark groove; S5, immersing the silicon wafer in a HF / HNO3 mixed solution for pretreatment, so that a porous silicon layer is formed on the surface of the silicon wafer; the mass concentration of HF in the HF / HNO3 mixed solution is greater than that of HNO3; S6, alkali velveting.
2. The texturing method according to claim 1, characterized in that: In S1, the silicon wafer is an N-type single crystal silicon wafer.
3. The texturing method according to claim 1, characterized in that: In S1, the laser wavelength of the laser primary crystallization treatment is 500-600 nm, the pulse time is 5-20 ns, the frequency is 10-20 KHz, the power is 1-5 W, and the time is 1-10 s.
4. The texturing method according to claim 1, characterized in that: In S2, The alkali concentration in the alkali polishing solution of the primary alkali polishing is 1.7-2.2 wt %; The temperature of the first alkali polishing is 75-85°C, the time is 1-5 min, and the thinning amount is 0.10-0.20 g.
5. The texturing method according to claim 1, characterized in that: In S3, the laser wavelength of the laser patterning secondary crystallization treatment is 500-600 nm, the pulse time is 5-20 ns, the frequency is 1-10 KHz, the power is 5-10 W, and the time is 1-20 s.
6. The texturing method according to claim 1, characterized in that: In S4, The alkali concentration in the alkali polishing solution of the secondary alkali polishing is 1.7-2.2 wt %; The temperature of the secondary alkali polishing is 75-85°C, the time is 1-3 min, and the thinning amount is 0.05-0.20 g.
7. The texturing method according to claim 1, characterized in that: In S5, the HF / HNO3 mixed solution is prepared by mixing 45-55 wt% HF solution and 65-75 wt% HNO3 solution in a volume ratio of 2:1-7:
1.
8. The texturing method according to claim 1, characterized in that: In S5, the pretreatment temperature is 30-35°C and the time is 30-120 s.
9. The texturing method according to claim 1, characterized in that: In S6, the alkali texturing uses 1.6-2.0 wt% alkali solution, the alkali texturing temperature is 75-85° C., and the time is 5-7 min.
10. The texturing method according to claim 1, characterized in that: In S6, the velvet surface size of the pyramid velvet surface formed after alkali texturing is 1~2 μm, and the surface reflectivity of the silicon wafer is less than 10%.
Citation Information
Cited By
Battery piece preparation method and battery piece
CN121099767A